Solar quiet current response in the African sector due to a 2009 sudden stratospheric warming event - Bolaji, O.J.; Oyeyemi, E.O.; Owolabi, O.P.; Yamazaki, Y.; Rabiu, A.B.; Okoh, D.; Fujimoto, A.; Amory-Mazaudier, C.; Seemala, Gopi K.; Yoshikawa, A.; Onanuga, O.K. (My University, 2016)
We present solar quiet (Sq) variation of the horizontal (H) magnetic field intensity deduced from Magnetic Data Acquisition System (MAGDAS) records over Africa during an unusual strong and prolonged 2009 sudden stratospheric warming (SSW) event. A reduction in the SqH magnitude that enveloped the geomagnetic latitudes between 21.13°N (Fayum FYM) in Egypt and 39.51°S (Durban DRB) in South Africa was observed, while the stratospheric polar temperature was increasing and got strengthened when the stratospheric temperature reached its maximum. Another novel feature associated with the hemispheric reduction is the reversal in the north-south asymmetry of the SqH, which is indicative of higher SqH magnitude in the Northern Hemisphere compared to the Southern Hemisphere during SSW peak phase. The reversal of the equatorial electrojet (EEJ) or the counter electrojet (CEJ) was observed after the polar stratospheric temperature reached its maximum. The effect of additional currents associated with CEJ was observed in the Southern Hemisphere at middle latitude. Similar changes were observed in the EEJ at the South America, Pacific Ocean, and Central Asia sectors. The effect of the SSW is largest in the South American sector and smallest in the Central Asian sector.
Keywords: Stratospheric sudden warming; Middle atmosphere; Magnetic Data Acquisition System; MAGDAS; Counter electrojet; Equatorial electrojet; SSW